Esej i ekfraza (Herbert - Bieńkowska - Bieńczyk) - Sendyka, Roma (Wydawnictwo Naukowe UAM, 2009)
Michel Riffaterre in article L'lllusion d'ekphrasis put forward an idea of "critical ekphrasis" (1994) what may become an invitation to ask if other sub-genres/modes of ekphrasis may be described. The text Essay and Ekphrasis develops this question in the field of essayistic traditions. Evoking the tendency of writing on art in that genre (from Montaigne, Diderot, Ruskin, Pater to art historians, critics and artists) the article analyses three examples of ekphrases (by Zbigniew Herbert, Ewa Bieńkowska and Marek Bieńczyk) to voice a hypothesis that ekphrasis in an essay may be a useful proof for those who question (ostensive) representational powers of that textual tool. Essayistic ekphrasis seems to have a foremost referential character, pointing towards an object of art only to use it in order to describe cognitive procedures of the subject who in such a way (performatively and not overtly) pictures himself mirroring his inner self in dispersed fragments of cultural object, dismantling the temporal and spatial difference between the viewer and the object in an illusion of an immediate presence. 1.
Essay and Ekphrasis (Herbert - Bieńkowska - Bieńczyk)